Land Use Change Analysis to Springs Conditions in Gunungpati Sub-District, Semarang City - Wahid Akhsin Budi Nur Sidiq; Tjaturahono Budi Sanjoto; Nana Kariada Tri Martuti (Department of Geography Education, University of Jember, 2022)
Semarang City has the fastest development in Central Java Province, where the activities are no longer centralized but have expanded to the upper part of the region. The ongoing development certainly impacts changes with the increasing area of built-up land that converts to another cover, such as vegetation. The phenomenon impacts the balance of the environment, one of which is the source of springs. Therefore, this study aims to map the spatial distribution of the springs and identify their physical quality. A quantitative approach was used with spatial analysis. Meanwhile, data collection techniques used document research, high-resolution image interpretation and field surveys. Field surveys were conducted to test the accuracy of land use maps and measurements of discharge, temperature, pH and brightness of the springs. The results showed that there is a change in land use from 2016 - 2021 with an increase in settlements of around 77.25 hectares and commercial service buildings by 178.79 hectares. For land use with the largest decrease in area, agricultural land covers and mixed garden/vegetation covers an area of ​​207.01 and 50.57 hectares. There were 114 springs at the research site, of which 5% of the springs had a relatively large discharge above 10 liters/second, while the other 47% had a small discharge. For pH conditions, there were 6 springs with a pH value of less than 6. Land use change from vegetation to flying land impacts the reduction of the water supply in the soil. The impact can be seen by the non-production of several springs, where 21 springs have not been discharged. In conclusion, there is a change in land use with an increase in built-up from 2016 - 2021 by 256.04 hectares. The increase in built-up is partly in conservation areas, hence damaging several springs. Keywords : Land use change; Springs conditions; Gunungpati Sub-District Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License